Effect of cassava (Manihot esculenta Crantz) varieties on leaf bud sprouting for rapid multiplication of planting materials - Meibuko, Ngakwi Masai; Mtui, Hosea Dunstan; Baltazari, Anna (Frontiers in Plant Science, 2025)
A drawback associated with conventional clonal propagation of cassava is its limited multiplication ratio, which poses challenges for both cassava crop enhancement and seed system initiatives. This study was aimed to evaluate the response of varieties on the sprouting ability of their leaf buds from the upper, middle, and lower positions of mature plant branches for rapid multiplication of planting materials. Five varieties, namely, Kizimbani, Mkombozi, Mkumba, TARICASS 4, and Mkuranga 1, were selected. The criteria for selection were resistance to green mites (Mononychellus tanajoa), a common cassava serious insect pest; Cassava Mosaic Disease (CMD) and Cassava Brown Streak Disease (CBSD), the most serious cassava viral diseases; and high-yielding, dry matter, and starch content potentials. The experiment was conducted in a screen house where the leaf buds from mature mother plant branches were planted in a growth cage measuring 3.0 m × 1.5 m × 3.5 m made of metal pipes and covered with a transparent polyethylene sheet for sprouting. The design used was randomized complete block design (RCBD) in a split–split plot arrangement with three replications. Varieties were the main plot factor, media as a subplot factor, and leaf bud position as a sub–sub plot factor. Results showed that variety had significant effects (p < 0.001) on number of nodes, percent sprouting, number of sprouts, and days to 50% sprouting, and a significant difference (p < 0.01) on percent survival rates and days to first sprouting. The effects of leaf bud position had significant effects (p < 0.001) on the number of leaf buds, percent sprouting, number of sprouts, days to first sprouting, and percent survival rates. The media used showed significant effects on days to first sprouting (p < 0.01) and first sprouting. TARICASS 4 was the most promising variety for rapid multiplication of cassava planting materials using the leaf bud technique due to its superior performance. The use of coco peat and peat moss media generally led to early and more successful sprouting. These results are important as a basis for selecting varieties for propagation using the leaf bud technique for rapid multiplication of planting materials for breeding and seed production purposes.